2019
DOI: 10.1016/j.ecoenv.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Elaeocarpus glabripetalus seedlings exposed to simulated acid rain and cadmium

Abstract: Combined effects of cadmium (Cd) and acid rain on physiological and biochemical characteristics in Eleocarpus glabripetalus seedlings were investigated under controlled conditions. The single Cd treatment and the combined Cd and acid rain treatment increased growth at low Cd concentrations, while decreased growth and photosynthesis at high Cd concentrations. A low Cd concentration (50mg‧kg -1 ) combined with different acid rain treatments increased the seedling biomass, while there was no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…We found that single acid rain treatments increased the PAL and CHT activities in leaves. Generally, acid rain stress can increase [ 11 ], or decrease POD activity depending on the stress intensity and duration [ 10 ]. The changes of POD activity in our study were in agreement with previous reports which suggested that increases in POD activity were observed in rice leaves under SAR of pH 5.0, 4.0, 3.0, and a decrease under SAR of pH 2.0 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that single acid rain treatments increased the PAL and CHT activities in leaves. Generally, acid rain stress can increase [ 11 ], or decrease POD activity depending on the stress intensity and duration [ 10 ]. The changes of POD activity in our study were in agreement with previous reports which suggested that increases in POD activity were observed in rice leaves under SAR of pH 5.0, 4.0, 3.0, and a decrease under SAR of pH 2.0 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that there would be a likely acidity threshold (pH ≥ 4.0) for rice defense system to acid rain stress, which would not affect the normal physiological activities of plants, but could improve the sensitivity of the plants’ resistance to stress. Below this threshold, the metabolic system would be destroyed and plant resistance would be reduced [ 11 ]. The changes in the contents of the flavonoids, total phenol and soluble sugar indicated that the single stress of inoculation with P. oryzae or acid rain increased the antioxidant metabolites, but the combined treatment stress of them under high acidity of simulated acid rain decreased and even inhibited the metabolites in rice seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations